A screening tool for the risk of disability retirement due to musculoskeletal disorders - Shiri, Rahman; Heliövaara, Markku; Ahola, Kirsi; Kaila-Kangas, Leena; Haukka, Eija; Kausto, Johanna; Saastamoinen, Peppiina; Leino-Arjas, Päivi; Lallukka, Tea (Scandinavian Journal of Work, Environment & Health, 2018)
' ' OBJECTIVE ': 'This study aimed to develop and validate a risk screening tool using a points system to assess the risk of future disability retirement due to musculoskeletal disorders (MSD). ' ' METHODS ': 'The development population, the Health 2000 Survey, consisted of a nationally representative sample of Finnish employees aged 30–60 years (N=3676) and the validation population, the Helsinki Health Study, consisted of employees of the City of Helsinki aged 40–60 years (N=6391). Both surveys were linked to data on disability retirement awards due to MSD from national register for an 11-year follow-up. ' ' RESULTS ': 'The discriminative ability of the model with seven predictors was good (Gönen and Heller’s K concordance statistic=0.821). We gave points to seven predictors: sex-dependent age, level of education, pain limiting daily activities, multisite musculoskeletal pain, history of arthritis, and surgery for a spinal disorder or carpal tunnel syndrome. A score of 3 or higher out of 7 (top 30% of the index) had good sensitivity (83%) and specificity (70%). Individuals at the top 30% of the risk index were at 29 [95% confidence interval (CI) 15–55) times higher risk of disability retirement due to MSD than those at the bottom 40%. ' ' CONCLUSION ': 'This easy-to-use screening tool based on self-reported risk factor profiles can help identify individuals at high risk for disability retirement due to MSD.
Keywords: disability retirement; MSD; musculoskeletal disease; musculoskeletal disorder; prediction; prevention; screening; screening tool